A nano-ampere current reference circuit in a 0.5 μm CDMOS technology. (August 2019) - Ding, Liqiang; Wang, Yang; Bao, Zhanying; Liao, Hanzhang; Jin, Xiangliang
Abstract: A low power current reference circuit with an enable-control terminal is presented in this work, which has been developed in 0.5 μm CDMOS technology. The circuit is capable of providing the reference current in a nano-ampere range for the supply voltage from 2 V to 3 V in the temperature range from −30 °C to 85 °C. The simulation and measurement results demonstrated that the reference current achieves the line regulation of 4.67 % /V, the average temperature coefficient of 361.59 ppm / °C when simulations and measurements are carried out for 8 die-samples under the same supply-voltage and temperature variations. The complete designed circuit consumes approximately 765.1 nA current to generate about 90 nA reference current at 3 V power supply while occupying an area of 0.0217 m m 2 .